Pengujian TPC, Kadar Air dan pH pada Ikan Tongkol (Euthynnus Affinis) Asap Cair Yang Disimpan Pada Suhu Ruang - Upet, Emanuel; Salindeho, Netty; Reo, Albert R; Montolalu, Lita; Kaparang, Josefa T; Makapedua, Daisy M; Dotulong, Verly (Sam Ratulangi University, 2021)
Mackarel Tuna fish (Euthynnus affinis) is a leading commodity as a source of food for people in North Sulawesi. The purpose of this study was to process mackarel tuna (Euthynnus affinis) using liquid smoke stored at room temperature and then tested the product quality, namely) water content, total plate count (TPC), and pH value. The results of the research the resulting moisture content ranged from 35.7 to 58.3%, according to the Indonesian National Standard (SNI) 2725: 2013 that the maximum water content of smoked fish with the maximum heat smoking method was 60%, the total plate count (TPC) was around The average total plate number of smoked fish produced is 0.52 x 10-4 to 2.83 x 10-5 cabbage / g, this value shows in accordance with SNI 2725: 2013 that the total plate number of smoked fish with the maximum heat smoking method is 5 x 104 kol / g, while the average pH value is 5.64, this value shows the pH of smoked fish is below neutral pH, so it can be concluded that the smoked fish contains acid. It is concluded that this research has fully met the requirements for public consumption so that it can be produced as a fishery product.